Sequence-Structure Comparative and Network-Based Prediction of Drought Gene Candidate Regulator in Elaeis guineensis - Permatasari, Galuh Wening; Putranto, Riza Arief; Mardhika, Larasati Dena; Aksa, Annisa Aulia; Setiawati, Yuli; Minarsih, Hayati; Riyadi, Imron; Ernayunita, Ernayunita (Journal of Tropical Biodiversity and Biotechnology, 2024)
Drought poses a significant threat to global food security, particularly impacting crops like oil palm. Selecting genes for genome editing to enhance drought tolerance presents formidable challenges. To ensure that the target gene is chosen correctly and results in the desired character, a pilot study is necessary to determine the target gene for knockout. Two genes drought-related, AtBRL3 and AtOST2, were scrutinized in this context. Aligned with the Elaeis guineensis genome, their neighbouring proteins and gene ontology were analysed to identify potential targets for genome editing. AtBRL3, identified as BRL1 (XP_010913986.1) in E. guineensis, exhibited 58.48% identity and 100% coverage. It interacts with 12 nodes, including BIR1, BRI1, and AT2G20050, crucial for signalling pathways and cellular responses. Molecular function analysis revealed kinase activity. AtOST2 showed high similarity to plasma membrane ATPase/HA1 (XP_010913679.1) in E. guineensis, with 87.46% identity and 100% query cover. It correlated with 14 genes associated with ABA stimulus, stomatal movement, and hormone response. EgBRL1 and EgHA1, resembling AtBRL3 and AtOST2, respectively, emerge as promising targets for developing drought-tolerant oil palm cultivars through gene editing. Nonetheless, further validation through in vitro gRNA target selection and in vivo conversion of OST2/BRL3-containing plasmids in oil palm calluses is indispensable to demonstrate their efficacy in conferring novel drought resistance traits.